A generalised distributed‐order Maxwell model. (29th June 2022) - Ferrás, Luís L.; Morgado, M. Luísa; Rebelo, Magda
Abstract : In this work, we present a generalised viscoelastic model using distributed‐order derivatives. The model consists of two distributed‐order elements (distributed springpots) connected in series, as in the Maxwell model. The new model generalises the fractional viscoelastic model presented by Schiessel and Blumen and allows for a more broad and accurate description of complex fluids when a proper weighting function of the order of the derivatives is chosen. We discuss the connection between classical, fractional and viscoelastic models of distributed order and highlight the fundamental concepts that support these constitutive equations. We also derive the relaxation modulus, the storage and loss modulus and the creep compliance for specific weighting functions.